ANALISIS CYBERBULLYING PADA PESERTA DIDIK KELAS VIII SMP NEGERI 13 PONTIANAK TAHUN AJARAN 2017/2018 - Afrianzi, Zigi; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research analyzed the cyberbullying on the students in class VIII Junior High School 6 Pontianak in academic year 2017/2018. The problems in this research were (1) What are the factors causing cyberbully doing cyberbullying? (2) What are the factors causing the students becoming the cyberbullying victims? (3) What are the effects of cyberbullying to cyberbully? (4) What are the effects of cyberbullying to victims? (5) What are the strategies to stop cyberbullying?. This research aimed to describe and find out about (1) The factors causing cyberbully doing cyberbullying? (2) The factors causing the students becoming the cyberbullying victims? (3) The effects of cyberbullying to cyberbully? (4) The effects of cyberbullying to victims? (5) The strategies to stop cyberbullying. The method used in this research was descriptive and survey research form. The population was the students of Junior High School 6 Pontianak class VIII in academic year 2017/2018 which was 28 students. This research used quantitative approach. The technique of data collection was indirect interview technique and it used questionnaire to collect the data. The result showed that cyberbullying on the students in class VIII junior high school 6 Pontianak was in moderate to high level. (1) The factor causing the students doing cyberbullying was 70% in moderate to high level, (2) The factors causing the students becoming the victims was 67% in moderate to high level, (3) The effect of cyberbullying to the cyberbully was 73% in moderate to high level, (4) The effect of cyberbullying to the victims was 71% in moderate to high level, (5) The strategies of counselling teacher to stop cyberbullying was74% in moderate to high level. Â Keywords: Analysis, Cyberbullying, Facebook As Social Media